The (declining) role of households in sustaining China's economy: Structural path analysis for 1997 - 2007 - Ling Yang; James Thurlow; Michael L. Lahr (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Current explanations for private consumption's diminished role in China focus on the expansion of exports and investments. Using structural path analysis, we find additional contributing factors. First, growth patterns during 1997-2007 favoured sectors with low production multipliers. Secondly, income multipliers fell in most sectors, especially in fast growing sectors and partly due to urbanization. This means less trickledown from growth to household incomes. Thirdly, households became less important in sustaining domestic production processes. Together, these deep structural changes suggest that enhancing private consumption's role in China will require new (services-oriented) growth patterns and a significant realignment of industry-household linkages.
Keywords: O12; R11; R15; 330; structural path analysis; economic growth; private consumption; China; Wirtschaftswachstum; Wirtschaftsstruktur; Gesamtwirtschaftlicher Konsum; China